Moderasi Beragama Menjawab Intoleransi di Dalam Peraturan Daerah Kota Banjarmasin Nomor 4 Tahun 2005 - Muhammad Torieq Abdillah; Ichwan Ahnaz Alamudi; Rahimah Tul Sa'dah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2023)
Abstract: In recent years, various acts of violence in the form of intolerance have turned out to be massive social phenomena under the pretext of being an excuse to legitimize acts of violence committed. In fact, from a national point of view, Indonesia has stipulated freedom of religion as stated in the Constitution, namely Article 28 of the 1945 Constitution. Apart from that, also in Banjarmasin City Regional Regulation No. 4 of 2005 is one of the sharia-based regional regulations. However, over time, this regional regulation experienced many violations in terms of violating its rules and discriminatory attitudes towards non-Muslim groups regarding freedom of religion and people's welfare. This study's normative juridical research method is a legal, conceptual, and case approach. The study results show that the regional regulation is contrary to the constitution because of the flawed material content coupled with cases that lead to discriminatory attitudes and intolerance when non-halal food stalls are also the target of raids during Ramadan. The existence of Al-Qur'an verses that discuss the concept of religious moderation can be a means of answering this problem. Keywords: Intolerance, Local Regulations, Religious Moderation Abstract: Beberapa tahun terakhir, berbagai tindakan kekerasan berupa intoleransi menjadi fenomena sosial masif dengan dalih menjadi alasan untuk melegitimasi tindakan kekerasan yang dilakukan. Padahal, jika dilihat dari sisi negara, Indonesia telah menetapkan kebebasan beragama sebagaimana tertuang di dalam UUD, yaitu Pasal 28 UUD 1945. Selain itu, juga di dalam Perda Kota Banjarmasin No. 4 Tahun 2005 merupakan salah satu Perda berbasis syariah. Namun, seiring berjalannya waktu, Perda ini justru mengalami banyak pelanggaran dalam hal melanggar aturan sendiri dan sikap diskriminatif terhadap kelompok nonmuslim dalam hal kebebasan beragama dan kesejahteraan rakyat. Metode penelitian yuridis normatif yang digunakan dalam penelitian ini adalah pendekatan hukum, konseptual, dan kasus. Hasil penelitian menunjukkan bahwa Perda tersebut dianggap bertentangan dengan konstitusi karena kandungan materi yang cacat ditambah kasus-kasus yang menyebabkan sikap diskriminatif dan intoleransi ketika warung makanan nonhalal juga menjadi sasaran razia selama Ramadan. Adanya ayat Al-Qur'an yang membahas konsep moderasi agama dapat menjadi sarana dalam menjawab permasalahan ini. Keywords: Intoleransi, Moderasi Beragama, Peraturan Daerah